Abuse liability and therapeutic potential of the Mitragyna speciosa (kratom) alkaloids mitragynine and 7‐hydroxymitragynine. (27th June 2018) - Hemby, Scott E.; McIntosh, Scot; Leon, Francisco; Cutler, Stephen J.; McCurdy, Christopher R.
Abstract: Kratom, derived from the plant Mitragyna speciosa, is receiving increased attention as an alternative to traditional opiates and as a replacement therapy for opiate dependence. Mitragynine (MG) and 7‐hydroxymitragynine (7‐HMG) are major psychoactive constituents of kratom. While MG and 7‐HMG share behavioral and analgesic properties with morphine, their reinforcing effects have not been examined to date. 7‐HMG, but not MG, substituted for morphine self‐administration in a dose‐dependent manner in the rat self‐administration paradigm. Following the substitution procedure, re‐assessment of morphine self‐administration revealed a significant increase following 7‐HMG and a significant decrease following MG substitution. In a separate cohort, 7‐HMG, but not MG, engendered and maintained intravenous self‐administration in a dose‐dependent manner. The effects of pretreatment with nalxonaxine (NLXZ), a μ1 opiate receptor antagonist, and naltrindole (NTI), a δ opiate receptor antagonist, on 7‐HMG and morphine self‐administration were also examined. Both NLXZ and NTI reduced 7‐HMG self‐administration, whereas only NLXZ decreased morphine intake. The present results are the first to demonstrate that 7‐HMG is readily self‐administered, and the reinforcing effects of 7‐HMG are mediated in part by μ and δ opiate receptors. In addition, prior exposure to 7‐HMG increased subsequent morphine intake whereas prior exposure to MG decreased morphine intake. The present findings indicate that MG does not have abuse potential and reduces morphine intake, desired characteristics of candidate pharmacotherapies for opiate addiction and withdrawal, whereas 7‐HMG should be considered a kratom constituent with high abuse potential that may also increase the intake of other opiates. Abstract : Kratom has received considerable attention due to the potential for abuse and the potential to reduce opiate intake. We investigated whether the kratom alkaloids, mitragynine (MG) and 7‐hydroxymitragynine (7‐HMG) would substitute for morphine and engender and maintain responding. We conclude that MG does not have abuse potential and reduces morphine intake, desired characteristics of candidate pharmacotherapies for opiate addiction and withdrawal, whereas 7‐HMG has a high abuse potential and may also increase the intake of other opiates.